Carotid Body Chemoreceptors: Physiology, Pathology, and Implications for Health and Disease - Iturriaga, Rodrigo; Alcayaga, Julio; Chapleau, Mark W; Somers, Virend K (Physiological reviews, 2021)
The carotid body (CB) is the main peripheral chemoreceptor for arterial respiratory gases O and CO and pH, eliciting reflex ventilatory, cardiovascular and humoral responses to maintain homeostasis. This review examines the fundamental biology underlying CB chemoreceptor function, its contribution to integrated physiologic responses, and its role in maintaining health and potentiating disease. Emphasis will be placed on: i) Transduction mechanisms in chemoreceptor (type I) cells, highlighting the role played by the hypoxic inhibition of O -dependent K channels and mitochondrial oxidative metabolism, and their modification by intracellular molecules and other ionic channels; ii) Synaptic mechanisms linking type I cells and petrosal nerve terminals, focusing on the role played by the main proposed transmitters and modulatory gases, and the participation of glial cells in regulation of the chemosensory process; iii) Integrated reflex responses to CB activation, emphasizing that the responses differ dramatically depending on the nature of the physiological, pathological or environmental challenges, and the interactions of the chemoreceptor reflex with other reflexes in optimizing oxygen delivery to the tissues; and iv) The contribution of enhanced CB chemosensory discharge to autonomic and cardiorespiratory pathophysiology in obstructive sleep apnea, congestive heart failure, resistant hypertension and metabolic diseases, and how modulation of enhanced CB reactivity in disease conditions may attenuate pathophysiology.